Separator for electrochemical device and electrochemical device comprising same
By using the heat-raising elution grading method in the separator of the electrochemical device, the problems of separator deformation and pore damage caused by pressure in the lamination process are solved, the insulation breakdown voltage is improved, and the battery performance is enhanced.
Patent Information
- Application Number
- CN202480002515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-22
- Filing Date
- 2024-03-19
- Publication Date
- 2024-12-20
AI Technical Summary
In the lamination process of the electrochemical device, the applied pressure causes deformation of the diaphragm and damage to the hole, reducing the insulation breakdown voltage, resulting in Hi-Pot and low voltage failures.
Using a porous polymer substrate, which contains amorphous polymer resin and a crystalline polymer resin, is prepared by heating elution grading method, adjusting the molecular weight and dispersion index of the polymer resin, increasing the content of the crystalline polymer resin, and ensuring that the membrane is at high temperature. It has high compression resistance and uniformity.
It effectively reduces deformation caused by pressure in the lamination process, improves insulation breakdown voltage, prevents Hi-Pot and low voltage failures, and enhances battery performance.
Smart Images

Figure CN119174043A_ABST
Abstract
Description
Technical Field
[0001] This application is based on and claims the benefit of priority of Korean Patent Application Nos. 10-2023-0051176, 10-2023-0055916 and 10-2023-0065754 filed on April 19, 2023, April 28, 2023 and May 22, 2023 in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0002] The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the separator. Background Art
[0003] The separator is one of the components of the electrochemical device, including a porous polymer substrate disposed between the positive electrode and the negative electrode, which plays the role of separating the positive electrode and the negative electrode from each other, preventing short circuits between the two electrodes, and allowing electrolytes and ions to pass through its pores. The separator itself does not participate in the electrochemical reaction, but its physical properties such as wettability to electrolytes, porosity, and thermal shrinkage will affect the performance and safety of the electrochemical device.
[0004] In order to improve the physical properties of the separator, various methods are being tried, such as forming a coating on the porous polymer substrate and adding various substances to the coating to change the physical properties of the coating. For example, an inorganic substance may be added to the coating to improve the mechanical strength of the separator, or an inorganic substance or hydrate may be added to the coating to improve the fire resistance and heat resistance of the polymer substrate. Summary of the invention
[0005] Technical issues
[0006] The present disclosure provides a diaphragm for an electrochemical device and an electrochemical device comprising the diaphragm, whereby the present disclosure can avoid deformation of the diaphragm and damage to the pores of the diaphragm caused by applied pressure during the lamination process of combining the diaphragm with an electrode, thereby improving the insulation breakdown voltage level of the diaphragm.
[0007] Advantages of the present disclosure are not limited to the above description, and a person of ordinary skill in the art to which the present disclosure pertains can clearly understand other advantages from the following description.
[0008] Technical Solution
[0009] An embodiment of the present disclosure provides a separator for an electrochemical device, comprising a porous polymer substrate, wherein the porous polymer substrate comprises a non-crystalline polymer resin and a crystalline polymer resin, and an eluate eluted from the porous polymer substrate by a temperature rising elution fractionation (TREF) method has a weight average molecular weight (Mw) of about 100,000 or more.
[0010] According to one embodiment of the present disclosure, the porous polymer substrate may include about 40 wt % or less of a fraction eluted by a TREF method at a temperature of 35° C. or less.
[0011] According to one embodiment of the present disclosure, the content of the non-crystalline polymer resin in the porous polymer substrate may be about 40 wt % or less.
[0012] According to one embodiment of the present disclosure, the content of the crystalline polymer resin in the porous polymer substrate may be about 60 wt % or more.
[0013] According to one embodiment of the present disclosure, a weight ratio of the non-crystalline polymer resin to the crystalline polymer resin in the porous polymer substrate may be about 1:1 to 10:1.
[0014] According to one embodiment of the present disclosure, the porous polymer substrate may have a deviation in indentation depth of about -5 nm to 5 nm.
[0015] According to one embodiment of the present disclosure, the porous polymer substrate may include a polyolefin-based resin, the non-crystalline polymer resin may be a non-crystalline polyolefin-based resin, and the crystalline polymer resin may be a crystalline polyolefin-based resin.
[0016] According to one embodiment of the present disclosure, the polyolefin-based resin may be one selected from the group consisting of polyethylene; polypropylene; polybutene; polypentene; polyhexene; polyoctene; at least one copolymer of ethylene, propylene, butene, pentene, 4-methylpentene, hexene, octene; and combinations thereof.
[0017] According to one embodiment of the present disclosure, the polyolefin-based resin may have an average short chain branch (SCB) of 500 or less per total 1,000 carbon atoms.
[0018] According to one embodiment of the present disclosure, the polyolefin-based resin may have a melt index (ASTM D1238, 190° C., 2.16 kg) of about 0.1 g / 10 min to 0.3 g / 10 min.
[0019] According to one embodiment of the present disclosure, the porous polymer substrate may have a weight average molecular weight (Mw) of about 500,000 to 3,000,000.
[0020] According to one embodiment of the present disclosure, the polydispersity index (PDI) of the eluate may be about 5 or more.
[0021] According to one embodiment of the present disclosure, when a pressure of 8 MPa is applied at 70° C., at least one of the following conditions (i) to (iii) may be satisfied:
[0022] (i) the thickness reduction rate of the porous polymer substrate defined by the following Formula 1 is about 10% or less:
[0023] [Formula 1]
[0024] Thickness reduction rate (%) = (thickness of porous polymer substrate before applying pressure - thickness of porous polymer substrate after applying pressure) / thickness of porous polymer substrate before applying pressure × 100;
[0025] (ii) the porous polymer substrate has a post-compression air permeability increase rate of about 185% or less as defined by the following formula 2:
[0026] [Formula 2]
[0027] Air permeability increase rate (%) = (air permeability after compression - air permeability before compression) / (air permeability before compression) × 100; and
[0028] (iii) The porous polymer substrate has a dielectric breakdown voltage of about 1,000 V or more.
[0029] According to one embodiment of the present disclosure, the porous polymer substrate may have a thickness of about 1 μm to 30 μm.
[0030] Another embodiment of the present disclosure provides an electrochemical device including: a positive electrode; a negative electrode; and the separator as described above, the separator being interposed between the positive electrode and the negative electrode.
[0031] Effects of the Invention
[0032] The separator for an electrochemical device according to one embodiment of the present disclosure can improve the weight average molecular weight and polydispersity index of an eluate eluted at a high temperature to minimize deformation caused by applied pressure in a lamination process, thereby improving an insulation breakdown voltage level.
[0033] The electrochemical device according to an embodiment of the present disclosure can prevent Hi-Pot (high potential) failure and low voltage failure, thereby enhancing battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a diagram schematically showing a method of measuring the indentation depth.
[0035] In the multiple views of the drawings, the same reference numerals represent the same constituent elements. The drawings presented are shown for simplicity and clarity and are not necessarily drawn to scale. For example, the dimensions of certain elements in the drawings may be exaggerated relative to other elements to help improve the understanding of the various embodiments. In addition, in order to facilitate a clearer observation of these various embodiments, common but well-understood elements that are useful or necessary in commercially feasible embodiments are generally not depicted. DETAILED DESCRIPTION
[0036] In the description herein, when a specific part “includes” specific constituent elements, the description does not mean that the specific part excludes other constituent elements, but means that the part may further include other constituent elements unless otherwise defined.
[0037] In the description herein, the expression "A and / or B" means "A and B, or A or B".
[0038] In the description herein, when a component is disposed “on” a specific portion, the description does not exclude the situation where another component is disposed between the component and the specific portion, but indicates that another component may also be disposed between the component and the specific portion, unless otherwise specified.
[0039] The terms "approximately," "about," and "substantially" as used herein are used to describe a range of values or degrees, or a meaning close thereto, taking into account inherent manufacturing and material tolerances, and are intended to prevent infringers from taking unfair advantage of the precise or absolute values in the present disclosure that are used to aid in understanding the present disclosure.
[0040] In the description herein, when an object includes "pores", the description means that the object has a plurality of pores that are interconnected, and the structure allows gas and / or liquid fluid to flow from one side of the object to the other side through the pores.
[0041] In the description herein, the separator has a porous property, contains a plurality of pores, and serves as a porous ion-conductive barrier that allows ions to pass through while blocking electrical contact between the negative electrode and the positive electrode in an electrochemical device.
[0042] The present disclosure will be described in more detail below.
[0043] In a secondary battery electrode assembly, a separator may be combined with an electrode through a lamination process, and in order to ensure a bonding force between the electrode and the separator, a polymer binder may be added to a coating composition of the separator.
[0044] On the other hand, when the process speed of the lamination process is increased in order to improve the process yield, there is a problem that the heating time is reduced, which may lead to a weakened bonding force. In order to improve the bonding force, a method of increasing pressure in the lamination process has been adopted. However, when a high pressure is applied to the diaphragm, the diaphragm may be deformed, for example, its thickness may be reduced. In addition, the pores may be destroyed, and as a result, the insulation breakdown voltage of the diaphragm may be reduced, which may cause Hi-Pot failure and low voltage failure.
[0045] The present disclosure provides a separator in which a polymer resin contained in a porous polymer substrate can be adjusted to prevent the separator from being reduced in thickness and to increase an insulation breakdown voltage.
[0046] In the polyethylene used for the porous substrate of the diaphragm, crystals and amorphous crystals coexist. When the crystal content is relatively high and its molecular weight distribution is narrow at this time, the compression resistance that affects the degree of change in the thickness of the material after compression is excellent. On the other hand, when propylene is added during the polyethylene polymerization process to improve the processability when manufacturing the polyethylene film, the content of amorphous crystals increases. In one embodiment of the present disclosure, propylene is not added during the polyethylene polymerization process or is added in a small amount less than or equal to the reference value, so that the content of crystals in the manufactured porous substrate is increased or adjusted, which can improve the general properties of the diaphragm, such as compression resistance.
[0047] One embodiment of the present disclosure provides a separator for an electrochemical device, comprising a porous polymer substrate prepared by the above method, wherein the porous polymer substrate comprises a non-crystalline polymer resin and a crystalline polymer resin, and when the porous polymer substrate is analyzed by a temperature rising elution fractionation (TREF) method, the eluted eluate has a weight average molecular weight (Mw) of about 100,000 or more.
[0048] As described above, when manufacturing a diaphragm for an electrochemical device according to one embodiment of the present disclosure, no or a small amount of propylene is added during the polymerization of polyethylene to increase or adjust the crystal content, which can improve the weight average molecular weight and polydispersity index of the eluate eluted at high temperature to minimize the deformation caused by the applied pressure during the lamination process, thereby improving the insulation breakdown voltage level.
[0049] One embodiment of the present disclosure relates to a diaphragm itself or a diaphragm for an electrochemical device in which the diaphragm can be used as a component. Therefore, as required, the diaphragm according to an embodiment of the present disclosure may include an additional layer on at least one surface of the porous polymer substrate that is different in material or function from the porous polymer substrate. For example, in one embodiment of the present disclosure, the diaphragm may include a coating containing inorganic particles and / or a polymer binder, such as an organic / inorganic composite layer, on at least one surface or both surfaces of the porous polymer substrate.
[0050] According to one embodiment of the present disclosure, the electrochemical device separator includes the porous polymer substrate. Since the electrochemical device separator includes the porous polymer substrate, the separator can allow lithium ions to pass while blocking electrical contact between the positive electrode and the negative electrode, and can also achieve closed-cell performance at an appropriate temperature. In the description herein, the "closed-cell performance" may refer to the ability of the porous polymer substrate to close the pores therein and block the passage of lithium ions through the separator under abnormally high temperature conditions.
[0051] According to one embodiment of the present disclosure, the porous polymer substrate includes the non-crystalline polymer resin and the crystalline polymer resin. For example, the polymer resin of the porous polymer substrate includes both crystalline and non-crystalline polymer resins, which may mean that the polymer resin includes a uniform mixture of non-crystalline and crystalline polymer resins, or one molecule of the polymer resin includes both non-crystalline and crystalline structures. In this way, since the porous polymer substrate includes the non-crystalline polymer resin and the crystalline polymer resin, the uniformity of the porous polymer substrate can be improved, and the compression resistance can be enhanced.
[0052] According to one embodiment of the present disclosure, the porous polymer substrate includes both crystalline and non-crystalline polymer resins by adjusting the addition of propylene during polyethylene polymerization, and when the porous polymer substrate is analyzed using a TREF method, the weight average molecular weight (Mw) of the eluted eluate is about 100,000 or more. For example, when the porous polymer substrate is analyzed by the TREF method, the weight average molecular weight (Mw) of the eluted eluate may be about 100,000 to 10,000,000, 200,000 to 9,000,000, 300,000 to 8,000,000, 400,000 to 7,000,000, 500,000 to 6,000,000, 600,000 to 5,000,000, 700,000 to 4,000,000, 800,000 to 3,000,000, 900,000 to 2,000,000, or 900,000 to 1,000,000. In this way, when the porous polymer substrate is analyzed using the TREF method, the weight average molecular weight (Mw) of the eluted eluate is adjusted to fall within the above range, so that the uniformity of the porous polymer substrate can be improved and the compression resistance can be enhanced.
[0053] According to one embodiment of the present disclosure, the eluate may be eluted using a TREF method at a temperature of about 90°C to 110°C. For example, the eluate may be eluted by a TREF method at a temperature of about 90°C to 110°C, 91°C to 109°C, 92°C to 108°C, 93°C to 107°C, 94°C to 106°C, 95°C to 105°C, 96°C to 104°C, 97°C to 103°C, 98°C to 102°C, or 99°C to 101°C. The porous polymer substrate of the present disclosure can improve the uniformity of the porous polymer substrate and enhance the compression resistance by adjusting the addition of propylene during the polyethylene polymerization process so that the polymer resin of the porous polymer substrate contains both crystalline and non-crystalline polymer resins, and also adjusting the temperature when the eluate of the porous polymer substrate is obtained by the TREF method as described above. In addition, the mechanical properties of the porous polymer substrate can be improved.
[0054] In the description of this article, "temperature rising elution fractionation (TREF)" analysis can be performed using the TREF instrument of Polymer Char. According to the TREF analysis, the sample can be melted and injected into the column at a high temperature, and then the temperature can be gradually reduced to induce sample crystallization. When the sample is precipitated in the column, the temperature can be increased to measure the molecular weight of the eluted sample. For example, 40 mg of a polymer sample is dissolved in 20 mL of a trichlorobenzene solvent at 150 ° C for 120 minutes and then stabilized at 100 ° C for 45 minutes. The stabilized sample is introduced into the TREF column, cooled to 35 ° C at a constant rate of 0.5 ° C / minute, and then kept for 15 minutes. Subsequently, the sample is heated from 35 ° C to 80 ° C at a constant rate of 20 ° C / minute, while maintaining it for 20 minutes at every 5 ° C increment, and also heated from 80 ° C to 120 ° C at a constant rate of 20 ° C / minute, while maintaining it for 20 minutes at every 2 ° C increment; the weight average molecular weight of the eluted polymer sample is measured to obtain a TREF analysis graph from the concentration measurement result.
[0055] According to one embodiment of the present disclosure, the porous polymer substrate may contain about 40% by weight or less of a fraction eluted by a TREF method at a temperature of 35°C or less. For example, when analyzed using the TREF method, the porous polymer substrate may contain a first fraction eluted at a temperature of 35°C or less and a second fraction eluted at a temperature of more than 35°C. The first fraction may contain the non-crystalline polymer resin. The second fraction is eluted from the porous polymer substrate by the TREF method at a temperature of more than 35°C, and may contain the crystalline polymer resin. For example, the second fraction may be eluted at a temperature of more than 35°C and less than 100°C, 40°C to 90°C, 50°C to 80°C, or 60°C to 70°C. In addition, the second fraction may be eluted at a temperature of 98°C or more.
[0056] According to one embodiment of the present disclosure, the content of the non-crystalline polymer resin in the porous polymer substrate may be about 40% by weight or less. For example, the content of the non-crystalline polymer resin in the porous polymer substrate may be about greater than 0% by weight and less than 40% by weight, 2% by weight to 38% by weight, 4% by weight to 36% by weight, 6% by weight to 34% by weight, 8% by weight to 32% by weight, 10% by weight to 30% by weight, 12% by weight to 28% by weight, 14% by weight to 26% by weight, 16% by weight to 24% by weight, or 18% by weight to 22% by weight. By adjusting the content of the non-crystalline polymer resin in the porous polymer substrate to fall within the above range, the uniformity of the porous polymer substrate can be improved, and the compression resistance can be enhanced. In addition, the mechanical properties of the porous polymer substrate can be improved.
[0057] According to one embodiment of the present disclosure, the content of the crystalline polymer resin in the porous polymer substrate may be about 60% by weight or more. For example, the content of the crystalline polymer resin in the porous polymer substrate may be about 60% by weight or more and less than 100% by weight, 62% by weight to 98% by weight, 64% by weight to 96% by weight, 66% by weight to 94% by weight, 68% by weight to 92% by weight, 70% by weight to 90% by weight, 72% by weight to 88% by weight, 74% by weight to 86% by weight, 76% by weight to 84% by weight or 78% by weight to 82% by weight. In addition, the content of the crystalline polymer resin in the porous polymer substrate may be about 70% by weight to 85% by weight. By adjusting the content of the crystalline polymer resin in the porous polymer substrate to fall within the above range, the uniformity of the porous polymer substrate can be improved, and the compression resistance can be enhanced. In addition, the mechanical properties of the porous polymer substrate can be improved.
[0058] According to one embodiment of the present disclosure, the weight ratio of the non-crystalline polymer resin to the crystalline polymer resin in the porous polymer substrate may be about 1:1 to 10:1. For example, the weight ratio of the non-crystalline polymer resin to the crystalline polymer resin in the porous polymer substrate may be about 1.5:1 to 9.5:1, 2.0:1 to 9.0:1, 2.5:1 to 8.5:1, 3.0:1 to 8.0:1, 3.5:1 to 7.5:1, 4.0:1 to 7.0:1, 4.5:1 to 6.5:1, or 5.0:1 to 6.0:1. By adjusting the weight ratio of the non-crystalline polymer resin to the crystalline polymer resin in the porous polymer substrate to fall within the above range, the uniformity of the porous polymer substrate may be improved, and the compression resistance may be enhanced. In addition, the mechanical properties of the porous polymer substrate may be improved.
[0059] According to one embodiment of the present disclosure, based on 100 wt % of the porous polymer substrate, the content of the crystalline polymer resin in the porous polymer substrate may be about 70 wt % or more and 85 wt % or less. By adjusting the content of the crystalline polymer resin in the porous polymer substrate to fall within the above range, the indentation depth of the porous polymer substrate can be reduced, and the deviation of the indentation depth can be minimized, thereby improving the insulation breakdown voltage level.
[0060] According to one embodiment of the present disclosure, the indentation depth of the porous polymer substrate may be about 20 nm or less. For example, the indentation depth of the porous polymer substrate may be about 0 nm to 20 nm, greater than 0 nm and less than 19 nm, 1 nm to 18 nm, 2 nm to 17 nm, 3 nm to 16 nm, 4 nm to 15 nm, 5 nm to 14 nm, 6 nm to 13 nm, 7 nm to 12 nm, 8 nm to 11 nm, or 9 nm to 10 nm. By adjusting the indentation depth of the porous polymer substrate to fall within the above range, the compression resistance of the porous polymer substrate can be enhanced, the thickness uniformity of the porous polymer substrate after the lamination process can be improved, and the thickness variation can be minimized.
[0061] In the description herein, the "indentation" is a technique for analyzing the mechanical properties of a material, which is performed by using a diamond indenter having various shapes to press into the material, and comparing and analyzing the indentation shape with the load at the time of indentation. The indentation test is not only a technique for measuring the fracture toughness or hardness of a material, but is also used as a research technique, and many research advances have been made recently in various directions, such as analyzing the elastic-plastic behavior and residual stress state of a material, testing the adhesion of a thin film, and analyzing fracture characteristics and phase changes. For example, when indenting a fine material such as the diaphragm of the present disclosure, nanoindentation can be used, using an indenter to apply a load in units of N (Newton) or less.
[0062] Figure 1 is a diagram schematically showing a method for measuring indentation depth. In the description herein, the "indentation depth" can be measured as follows: After setting Dimension Icon (manufactured by Bruker Corporation) to the following conditions, Figure 1 The peak tapping force was measured while moving the tip relative to the sample surface, and an atomic force microscope (AFM, OSTASPA-R3, Bruker, f=300 kHz, k=26 N / m) was used to measure the depth to which the tip penetrated the sample surface when the peak tapping force was measured.
[0063] -Mode: Tapping (peak force QNM)
[0064] - Scanning speed: 0.3 Hz
[0065] -Peak force set point: 100 nN, Amplitude: 300 nm
[0066] - Scanning angle: 90°
[0067] According to one embodiment of the present disclosure, the deviation of the indentation depth of the porous polymer substrate may be about -5nm to 5nm. For example, the deviation of the indentation depth of the porous polymer substrate may be about -4nm to 4nm, -3nm to 3nm, -2nm to 2nm, -1nm to 1nm, -0.5nm to 0.5nm or -0.1nm to 0.1nm. In the description herein, the deviation refers to the difference of the variable relative to the average value, which can represent the difference between the indentation depth at a specific position of the porous polymer substrate and the average indentation depth of the porous polymer substrate. By adjusting the deviation of the indentation depth of the porous polymer substrate to fall within the above range, the insulation breakdown voltage of the porous polymer substrate can be increased.
[0068] According to one embodiment of the present disclosure, the porous polymer substrate may include a polyolefin-based resin. Since the porous polymer substrate includes the polyolefin-based resin, a separator for an electrochemical device may be easily formed, and closed-cell performance may be achieved when a high temperature occurs during battery operation.
[0069] According to one embodiment of the present disclosure, the non-crystalline polymer resin may be a non-crystalline polyolefin-based resin. In the description herein, the "non-crystalline" may refer to a state in which molecules are arranged in a disordered manner. As described above, the non-crystalline polyolefin-based resin is selected as the non-crystalline polymer resin so that closed-cell performance can be achieved when high temperatures occur during battery operation.
[0070] According to one embodiment of the present disclosure, the crystalline polymer resin may be a crystalline polyolefin-based resin. In the description herein, the "crystallization" may refer to a state in which molecules are arranged in an orderly manner. As described above, the crystalline polyolefin-based resin is selected as the crystalline polymer resin, thereby improving the mechanical properties of the porous polymer resin and enhancing the compression resistance.
[0071] In the description herein, "crystallinity" may refer to the content of crystals eluted above about 98°C when measured by TREF.
[0072] According to one embodiment of the present disclosure, the polyolefin resin may be one selected from the group consisting of polyethylene, polypropylene, polybutene, polypentene, polyhexene, polyoctene, copolymers of one or more of ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene, and combinations thereof. For example, the polyolefin resin may be polyethylene. By selecting the polyolefin resin from the above materials, the porous polymer substrate may include the crystalline polymer resin and the non-crystalline polymer resin, and as a result, the mechanical properties and compression resistance of the porous polymer substrate may be enhanced.
[0073] According to one embodiment of the present disclosure, the polyolefin contained in the polyolefin resin may have an average short chain branch (SCB) of about 500 or less per 1,000 carbon atoms in total. The number of short chain branches may be the number of methyl groups per 1,000 carbon atoms in total (CH3 / 1,000 TC). The short chain branches may interfere with the formation of the crystal structure during the polymer crystallization process, which may affect the characteristics of the substrate. The number of short chain branches can be controlled by adjusting the type and content of the monomers contained in the polyolefin substrate. For example, the number of short chain branches contained in the polyolefin substrate can be controlled by adjusting the type and content of the polyolefin polymer resin used in the polymerization process of the polymer resin for the polyolefin substrate and / or the film forming process using the polymer resin. For example, the number of short chain branches can be increased by increasing the content of, for example, propylene or butene during the polymerization process of the polyolefin polymer resin, or by adding, for example, polypropylene during the film forming process. The number of short chain branches can be confirmed by comparing the resins contained in the fractions eluted at different temperatures when performing TREF analysis. For example, the number of short chain branches can be confirmed by calculating the number of CH3 per about 1,000 carbon atoms using an IR detector and CH, CH2, CH3 filters for TREF analysis. For example, in the polyolefin substrate, the average number of short chain branches may be about 100 to 500, 150 to 450, 200 to 400, or 250 to 350 for every total of about 1,000 carbon atoms. In addition, in the polyolefin substrate, the average number of short chain branches per total of 1,000 carbon atoms may be 400 or less. When the number of average short chain branches exceeds the above range, the orientation of the polyolefin-based polymer resin contained in the polyolefin substrate may become unsatisfactory. By adjusting the number of the average short chain branches to fall within the above range, the crystalline polyolefin-based polymer resin can be satisfactorily oriented, thereby providing a polyolefin substrate that exhibits compression resistance in a lamination process.
[0074] According to one embodiment of the present disclosure, the polyolefin-based resin may have a melt index of about 0.1 g / 10 min to 0.3 g / 10 min. The melt index can be measured and calculated using ASTM D1238 as follows: the sample is placed in a cylinder and then heated to about 190°C, or the heated sample is placed in a cylinder, a piston is inserted to apply a load of about 2.16 kg, and the weight of the resin discharged from the orifice (inner diameter: 2.09 mm, length: 8 mm) disposed on the opposite side of the piston is measured and converted into a throughput of 10 minutes. By adjusting the melt index of the polyolefin to fall within the above range, the rigidity of the porous polymer substrate containing the polyolefin-based resin can be determined, thereby providing a porous polymer substrate that exhibits compression resistance in a lamination process.
[0075] According to one embodiment of the present disclosure, the weight average molecular weight (Mw) of the porous polymer substrate may be about 500,000 to 3,000,000. For example, the weight average molecular weight (Mw) of the porous polymer substrate may be about 500,000 to 2,500,000, or about 1,000,000 to 2,000,000. By adjusting the weight average molecular weight (Mw) of the porous polymer substrate to fall within the above range, the mechanical properties and compression resistance of the porous polymer substrate can be improved. In addition, when a mixture of different types of polyolefin resins is used, or when the diaphragm has a multilayer structure comprising different types of polyolefin resins, the weight average molecular weight of the polyolefin resin can be calculated by adding the weight average molecular weights corresponding to the content ratios of different types of polyolefin resins.
[0076] In the description herein, the weight average molecular weight (Mw) and the polydispersity index may be measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies), and the measurement conditions may be set as follows.
[0077] - Column: PL Olexis (Polymer Laboratories)
[0078] -Solvent: TCB (trichlorobenzene)
[0079] - Flow rate: 1.0 ml / min
[0080] -Sample concentration: 1.0 mg / mL
[0081] -Injection volume: 200μL
[0082] - Column temperature: 160℃
[0083] -Detector: Agilent high temperature RI detector
[0084] -Standard: Polystyrene (calibrated with cubic function)
[0085] According to one embodiment of the present disclosure, other resin components may be mixed as needed on the basis of the polyolefin resin, for example, filler particles may be included on the basis of the resin component. The filler particles may be introduced to act as a pressure barrier to prevent the thickness, pore size and air permeability of the diaphragm substrate from being excessively reduced due to the high pressure applied in the lamination process described later. The filler particles may include organic or inorganic fillers, each of which has a predetermined particle size, and are not limited to specific components, as long as they have a strength equal to or greater than that of the polyolefin resin.
[0086] According to one embodiment of the present disclosure, the porous polymer substrate can be manufactured by the following method (wet method): a polyolefin resin and a diluent are kneaded at a high temperature to form a single phase, the polymer material is separated from the diluent by a cooling process, the diluent is extracted to form pores, and then the polymer material is stretched and thermally fixed.
[0087] According to one embodiment of the present disclosure, a person skilled in the art can easily prepare the average size and maximum size of the pores of the diaphragm suitable for the scope of the present disclosure by adjusting, for example, the mixing ratio of the diluent, the stretching ratio and the temperature of the heat fixing process.
[0088] According to one embodiment of the present disclosure, the size of the pores can be calculated from the pore size distribution measured using a capillary flow porometer. For example, the diaphragm to be measured is first wetted with a wetting agent (e.g., Galwick solution), and then the air pressure on one side of the substrate is gradually increased. When the applied air pressure becomes greater than the capillary attraction of the wetting agent filled in the pores, the wetting agent that blocks the pores is pushed out, so that the size and distribution of the pores can be measured based on the pressure and flow rate when the wetting agent is pushed out, and the average pore size and the maximum pore size can be confirmed.
[0089] The porous polymer substrate may include pores with an average diameter of about 0.01 μm to 1 μm. For example, the size of each pore included in the porous polymer substrate may be about 0.01 μm to 0.09 μm, 0.02 μm to 0.08 μm, 0.03 μm to 0.07 μm, or 0.04 μm to 0.06 μm. By adjusting the pore size of the porous polymer substrate to fall within this range, the overall air permeability and ion conductivity of the manufactured membrane can be controlled.
[0090] According to one embodiment of the present disclosure, the polydispersity index (PDI) of the eluate may be about 5 or more. For example, the polydispersity index (PDI) of the eluate may be about 6 to 19, 7 to 18, 8 to 17, 9 to 16, 10 to 15, 11 to 14, or 12 to 13. By adjusting the polydispersity index of the eluate to fall within this range, the uniformity of the crystalline polymer resin may be improved, and the compression resistance may be enhanced.
[0091] According to one embodiment of the present disclosure, when a pressure of 8 MPa is applied at about 70° C., the separator may satisfy one or more of the following conditions (i) to (iii).
[0092] (i) The thickness reduction rate of the porous polymer substrate defined by the following Formula 1 may be about 10% or less.
[0093] [Formula 1]
[0094] Thickness reduction rate (%) = (thickness of porous polymer substrate before pressure application - thickness of porous polymer substrate after pressure application) / thickness of porous polymer substrate before pressure application × 100
[0095] For example, when a pressure of 8 MPa is applied at about 70° C., the thickness reduction rate of the porous polymer substrate according to Formula 1 above may be about 0% to 10%, 1% to 9%, 2% to 8%, 3% to 7%, or 4% to 6%. By making the thickness reduction rate of the porous polymer substrate within the above range, the compression resistance of the separator can be enhanced.
[0096] The porous polymer substrate may have a post-compression air permeability increase rate defined by the following Formula 2 of about 185% or less.
[0097] [Formula 2]
[0098] Air permeability increase rate (%) = (air permeability after compression - air permeability before compression) / (air permeability before compression) × 100
[0099] The compression resistance of the porous polymer substrate can be determined according to the rate of change of the air permeability before and after the compression of the substrate. Before compression, the air permeability of the porous polymer substrate may be about 10s / 100cc to 100s / 100cc. For example, the air permeability of the porous polymer substrate may be 10s / 100cc to 90s / 100cc, 20s / 100cc to 80s / 100cc, 30s / 100cc to 70s / 100 or 40s / 100cc to 60s / 100cc. In addition, the air permeability of the porous polymer substrate may be about 50s / 100cc to 80s / 100cc. When the air permeability of the porous polymer substrate falls within the above range, the air permeability range of the manufactured separator may be within a range suitable for ensuring the power output and cycle characteristics of the electrochemical device.
[0100] In addition, when a pressure of 8 MPa is applied at 70° C. for about 10 seconds to compress the porous polymer substrate, the air permeability increase rate after compression may be about 0% to 180%, 20% to 160%, 40% to 140%, 60% to 120%, 80% to 100%. In addition, after compression, the air permeability of the porous polymer substrate may be about 200s / 100cc or less. When the air permeability increase rate of the porous polymer substrate falls within the above range, the occurrence of defects caused by its deformation in the lamination process can be reduced. Under the above conditions, when a substrate exhibiting an air permeability greater than about 200s / 100cc after compression is used, the power output and cycle characteristics of the electrochemical device may be reduced.
[0101] The air permeability (s / 100cc) refers to the time (seconds) taken for about 100cc of air to pass through the porous polymer substrate or the separator having a predetermined area at a predetermined pressure. The air permeability can be measured using an air permeability tester (Gurley air permeability meter) according to ASTM D 726-58, ASTM D726-94, or JIS-P8117. For example, Gurley's 4110N device can be used at an air pressure of about 0.304 kPa or about 1.215 kN / m 2 About 100cc of air is measured under water pressure through a diameter of about 1 inch 2 (or about 6.54cm 2 ) of the sample. Alternatively, for example, an Asahi Seico EG01-55-1MR device can be used to measure the flow of about 100 cc of air through a 1-inch glass at room temperature under a constant water pressure of 4.8 inches. 2 The sample time.
[0102] (iii) The porous polymer substrate may have an insulation breakdown voltage of about 1,000 V or more.
[0103] For example, when a pressure of 8 MPa is applied at about 70° C., the insulation breakdown voltage of the porous polymer substrate may be about 1,000 V to 2,000 V, 1,100 V to 1,900 V, 1,200 V to 1,800 V, 1,300 V to 1,700 V, or 1,400 V to 1,600 V. By adjusting the insulation breakdown voltage of the porous polymer substrate to fall within the above range, the insulation performance of the porous polymer substrate may be improved.
[0104] In the description herein, the insulation breakdown voltage may refer to a voltage when a current exceeds about 0.5 mA and 3 seconds while increasing an applied voltage at a rate of about 100 mV / s for a sample having a thickness of about 12 μm.
[0105] According to one embodiment of the present disclosure, the thickness of the porous polymer substrate may be about 1 μm to 30 μm. For example, the thickness of the porous polymer substrate may be about 2 μm to 29 μm, 3 μm to 28 μm, 4 μm to 27 μm, 5 μm to 26 μm, 6 μm to 25 μm, 7 μm to 24 μm, 8 μm to 23 μm, 9 μm to 22 μm, 10 μm to 21 μm, 11 μm to 20 μm, 12 μm to 19 μm, 13 μm to 18 μm, 14 μm to 17 μm or 15 μm to 16 μm. By adjusting the thickness of the porous polymer substrate to fall within the above range, the energy density of the electrochemical device separator can be improved.
[0106] The method for manufacturing the porous polymer substrate according to one embodiment of the present disclosure may include: kneading and extruding the porous polymer substrate composition containing the polymer resin; cooling the extruded porous polymer substrate composition to form a sheet; stretching the sheet; forming pores in the stretched sheet; and thermally fixing the sheet having the pores formed therein to manufacture the porous polymer substrate. By manufacturing the porous polymer substrate in this manner, the porous polymer substrate having uniform pores can be provided.
[0107] According to one embodiment of the present disclosure, the method for manufacturing the porous polymer substrate may include kneading and extruding the porous polymer substrate composition containing the polymer resin. As described above, by including the steps of kneading and extruding, a uniform porous polymer substrate composition can be prepared, thereby preparing a porous polymer substrate with a uniform pore size.
[0108] According to one embodiment of the present disclosure, the composition for porous polymer substrate may further include a diluent. For example, the diluent may be liquid paraffin oil. When such a diluent is included, the diluent may be easily removed from the sheet and the denaturation of the polymer resin may be prevented.
[0109] According to one embodiment of the present disclosure, the liquid paraffin oil may have a kinematic viscosity of about 30 to 50 cSt at 40° C. By using the liquid paraffin oil having a kinematic viscosity falling within the above range, the concentration of the diluent in the composition for a porous polymer substrate may be adjusted to be uniform.
[0110] According to one embodiment of the present disclosure, the weight ratio of the polymer resin to the diluent in the composition for porous polymer substrate may be about 2: 8 to 5: 5. By adjusting the weight ratio of the polymer resin to the diluent in the composition for porous polymer substrate to fall within the above range, the air permeability of the porous polymer substrate may be adjusted.
[0111] According to one embodiment of the present disclosure, the extrusion may be performed through a T-die of a twin-screw extruder. By performing the extrusion in this manner, the thickness of the sheet may be easily adjusted, and the cooling efficiency may be improved.
[0112] According to one embodiment of the present disclosure, the method for manufacturing the porous polymer substrate may include cooling an extruded porous polymer substrate composition to form a sheet.
[0113] According to one embodiment of the present disclosure, the cooling temperature of the sheet may be about 40° C. to 80° C. For example, the temperature cast onto the roller through the T-die may be about 40° C. to 80° C. By adjusting the cooling temperature of the sheet to fall within this range, the crystalline polymer resin may be obtained, and by adjusting the contents of the crystalline polymer resin and the non-crystalline polymer resin in the porous polymer resin, the indentation depth may be reduced, and the standard deviation of the indentation depth may be minimized.
[0114] According to one embodiment of the present disclosure, the method for manufacturing the porous polymer substrate may include stretching the sheet. By including the stretching step, the thickness of the porous polymer substrate may be adjusted, so that the sheet may be made into a thin film.
[0115] According to one embodiment of the present disclosure, the stretching can be performed bidirectionally using a tenter-type synchronous stretching machine. For example, the sheet can be stretched in the longitudinal direction (MD) and then in the transverse direction (TD). By performing the stretching step in this manner, the sheet can be made into a large-area porous polymer substrate.
[0116] According to one embodiment of the present disclosure, the method for manufacturing the porous polymer substrate may include forming pores in a stretched sheet. For example, in order to form pores in the stretched sheet, a solvent may be used to remove the diluent contained in the porous polymer substrate. The solvent may be dichloromethane. By including the step of forming pores in the stretched sheet as described above, the porous polymer substrate may be manufactured, and the residual diluent may be minimized.
[0117] According to one embodiment of the present disclosure, the method for manufacturing the porous polymer substrate may include heat-fixing the sheet having pores formed therein. For example, the temperature for heat-fixing the sheet may be about 100° C. to 150° C. By heat-fixing the sheet in this manner, the heat resistance of the separator may be improved.
[0118] According to one embodiment of the present disclosure, the separator for an electrochemical device may further include a coating layer formed on at least one surface of the porous polymer substrate.
[0119] According to one embodiment of the present disclosure, the coating comprises a polymer binder and inorganic particles and has a porous characteristic.
[0120] According to one embodiment of the present disclosure, the coating may be a porous coating including a plurality of pores. For example, the coating may be a porous coating having a plurality of pores therein. When the coating has a plurality of pores as described above, the separator containing the coating may allow the passage of lithium ions to allow current to flow while physically separating the negative electrode and the positive electrode.
[0121] According to one embodiment of the present disclosure, the weight ratio of the polymer binder and the inorganic particles contained in the coating layer may be about 1:99 to 30:70. The ratio may be appropriately adjusted within the above range, and when the sum of the polymer binder and the inorganic particles is 100 wt %, the polymer binder may be about 1 wt % or more, 5 wt % or more, or 10 wt % or more, and the inorganic particles may be about 80 wt % or more, 85 wt % or more, 90 wt % or more, or 95 wt % or more.
[0122] According to one embodiment of the present disclosure, the coating layer may be formed in such a manner that inorganic particles are bound by a polymer binder and aggregated in a layer. The pores in the coating layer may be formed by interstitial volumes that are voids between the inorganic particles.
[0123] In one embodiment of the present disclosure, the air permeability of the coating may be about 30% to 70% by volume. When the air permeability of the coating is about 70% by volume or less, the mechanical properties that can withstand the pressing process for combining with the electrode can be ensured, and since the surface opening rate is not too high, the bonding force can be ensured. On the other hand, when the air permeability of the coating is about 30% by volume or more, it is advantageous from the perspective of ion permeability.
[0124] In the description herein, the air permeability of the coating refers to the ratio of the volume occupied by pores to the total volume of the coating, and the unit "volume %" is used, which can be used interchangeably with the terms "void ratio", "porosity" and the like.
[0125] In the description herein, the air permeability corresponds to a value obtained by subtracting a volume converted from the weight and density of each component of the porous polymer substrate and the coating from a volume calculated using the thickness, length, and width of the porous polymer substrate and the coating.
[0126] For example, the porous polymer substrate may have an air permeability of about 10% to 60% by volume. According to one embodiment, the air permeability of the porous polymer substrate may be about 15% to 55% by volume, 20% to 50% by volume, 25% to 45% by volume, or 30% to 40% by volume. When the air permeability of the porous polymer substrate falls within this range, the ionic conductivity range of the manufactured separator may be within a range suitable for ensuring the power output and cycle characteristics of the electrochemical device.
[0127] In one embodiment of the present disclosure, the air permeability and pore size of the porous polymer substrate and the coating can be measured by a BET six-point method according to a nitrogen adsorption distribution method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porosimeter, or a porosity analyzer (Bell Japan Co., Ltd. Belsorp-II mini). It may be advantageous to use a capillary flow porosimeter.
[0128] According to one embodiment of the present disclosure, the thickness of the coating layer on either side of the porous polymer substrate may be about 1 μm to 20 μm, but the thickness is not particularly limited thereto. Those skilled in the art may adjust the thickness within a suitable range in consideration of heat resistance or electrical resistance.
[0129] According to one embodiment of the present disclosure, the thickness of the porous polymer substrate and / or the coating can be measured using a contact thickness gauge, such as VL-50S-B manufactured by Mitutoyo Corporation.
[0130] According to one embodiment of the present disclosure, the polymer binder that can be used for the coating may be any polymer resin selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose or a mixture of two or more polymer resins. However, the present disclosure is not limited thereto.
[0131] In one embodiment of the present disclosure, the inorganic particles that can be used for the coating are not particularly limited as long as they have electrochemical stability. For example, in one embodiment of the present disclosure, the inorganic particles that can be used are not particularly limited as long as they are within the operating voltage range of the applied electrochemical device (e.g., based on Li / Li + No oxidation and / or reduction reaction occurs within the range of 0V to 5V).
[0132] According to one embodiment of the present disclosure, non-limiting examples of the inorganic particles include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT,0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3)O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), zinc tin oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4) and antimony pentoxide (Sb2O5), and the inorganic particles may contain more than one of them.
[0133] According to one embodiment of the present disclosure, the average diameter (D 50 ) is not particularly limited, but may be in the range of about 0.3 μm to 1 μm to form a coating having a uniform thickness and ensure an appropriate porosity. For example, when the average diameter is less than about 0.3 μm, the dispersibility of the inorganic particles in the slurry prepared for forming the coating may be deteriorated, and when the average diameter is greater than about 1 μm, the thickness of the formed coating may increase.
[0134] In the description of this article, "particle size D 50 " refers to the particle size at about 50% point in the cumulative distribution of the number of particles according to the particle size. The particle size can be measured using a laser diffraction method. For example, the powder to be tested is dispersed in a dispersion medium, and then placed in a commercially available laser diffraction particle size measuring instrument (such as Microtrac S3500), and the difference in the diffraction pattern according to the particle size when the particles pass through the laser beam is measured to calculate the particle size distribution. Particle size D 50 It can be measured by calculating the particle size at the point corresponding to 50% of the cumulative distribution of the number of particles in the measurement device.
[0135] According to one embodiment of the present disclosure, the method for forming the coating is, for example, as follows. First, the polymer binder is dissolved in a suitable organic solvent to prepare a polymer solution, or is dispersed in a suitable dispersion medium to prepare a polymer emulsion. The organic solvent or dispersion medium that can be used may have a solubility index similar to the polymer binder to be used, and may have a low boiling point. This is conducive to uniform mixing and subsequent removal of the solvent or dispersion medium. Non-limiting examples of solvents that can be used include acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water, and mixtures thereof.
[0136] Next, the inorganic particles are added to the prepared polymer solution and / or polymer dispersion medium and dispersed to prepare a coating slurry. According to one embodiment of the present disclosure, the content ratio of the inorganic particles and the polymer binder is the same as above, and is appropriately adjusted considering the thickness, pore size and air permeability of the coating of the present disclosure to be finally manufactured.
[0137] Next, the coating slurry prepared above is applied to at least one side of the prepared porous polymer substrate, and then dried. The method of applying the slurry to the surface of the porous polymer substrate is not limited to a specific method, and a common method known in the art can be used. For example, various methods including dip coating, die coating, roller coating, comma coating and combinations thereof can be used.
[0138] For the drying process, the temperature and time conditions are appropriately set to minimize the generation of surface defects of the coating. Drying can be performed using a drying auxiliary means such as a drying furnace or hot air within an appropriate range.
[0139] When the separator includes the coating layer, damage of the surface of the porous polymer substrate facing the coating layer caused by compression of the inorganic particles may be reduced during a lamination process.
[0140] According to one embodiment of the present disclosure, the electrochemical device is manufactured by a lamination process, wherein the separator is inserted between the negative electrode and the positive electrode, and heat and / or pressure is applied to combine the separator and the electrode. In one embodiment of the present disclosure, the lamination process can be performed by a rolling device comprising a pair of pressing rollers. That is, the negative electrode, the separator and the positive electrode can be stacked in sequence, and the stacking material can be inserted between the pressing rollers to achieve interlayer bonding. In this case, the lamination process can be performed using a hot pressing method.
[0141] One embodiment of the present disclosure provides an electrochemical device including: a positive electrode; a negative electrode; and a separator manufactured as described above, the separator being interposed between the positive electrode and the negative electrode.
[0142] An electrochemical device according to one embodiment of the present disclosure can prevent Hi-Pot failure and low voltage failure, thereby improving battery performance.
[0143] In the present disclosure, the electrochemical device is a device that converts chemical energy into electrical energy through an electrochemical reaction, and conceptually covers primary batteries and secondary batteries. In the description herein, the secondary battery is rechargeable and represents, for example, a lithium secondary battery, a nickel-cadmium battery, and a nickel-metal hydride battery. The lithium secondary battery uses lithium ions as an ion conductor and may include, but is not limited to, a non-aqueous electrolyte secondary battery with a liquid electrolyte, an all-solid-state battery with a solid electrolyte, a lithium polymer battery with a gel polymer electrolyte, a lithium metal battery using lithium metal as a negative electrode, and the like.
[0144] According to one embodiment of the present disclosure, the positive electrode comprises: a positive electrode current collector; and a positive electrode active material layer, which is disposed on at least one surface of the current collector and comprises a positive electrode active material, a conductive agent and a binder resin. The positive electrode active material may comprise one compound or a mixture of two or more compounds selected from the group consisting of: a layered compound, such as: a lithium manganese composite oxide (such as LiMn2O4 and LiMnO2), a lithium cobalt oxide (such as LiCoO2) and a lithium nickel oxide (such as LiNiO2), or a compound substituted with one or more transition metals; a lithium manganese oxide, such as a compound of formula Li 1+x Mn 2-x O4 (wherein x represents 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxides (such as Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; compounds of the formula LiNi 1-x M x Nickel-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); represented by the formula LiMn1-xM x Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions; disulfide compounds; and Fe2(MoO4)3.
[0145] According to one embodiment of the present disclosure, the negative electrode includes: a negative electrode current collector; and a negative electrode active material layer, which is disposed on at least one surface of the negative electrode current collector and includes a negative electrode active material, a conductive agent, and a binder resin. The negative electrode may include a compound or a mixture of two or more compounds selected from the following as the negative electrode active material: lithium metal oxide and carbon (such as hard carbon and graphite carbon); metal composite oxides such as LixFe2O3 (0≤x≤1), Li x WO2(0≤x≤1) and Snx Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2, and 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; and titanium oxides.
[0146] According to one embodiment of the present disclosure, the conductive agent may be, for example, any one conductive material selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon, polyphenylene derivative, or a mixture of two or more conductive materials. The conductive agent may also be one conductive material selected from the group consisting of natural graphite, artificial graphite, super-P, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, denkablack, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, or a mixture of two or more conductive materials.
[0147] According to one embodiment of the present disclosure, the current collector only needs to have high conductivity and not cause chemical changes in the battery, and there is no particular limitation. It may be, for example, stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc.
[0148] According to one embodiment of the present disclosure, the binder resin may be a polymer commonly used for electrodes in the art. Non-limiting examples of the binder resin include, but are not limited to: polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trichloroethylene copolymer, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose.
[0149] In one embodiment of the present disclosure, the positive electrode paste for preparing the positive electrode active material layer may contain a dispersant, and the dispersant may be a pyrrolidone-based compound. For example, the dispersant may be N-methylpyrrolidone (ADC-01, LG Chem).
[0150] According to one embodiment of the present disclosure, based on 100 parts by weight of the positive electrode slurry, the content of the dispersant in the positive electrode slurry may be greater than about 0 parts by weight and less than 0.5 parts by weight. For example, based on 100 parts by weight of the positive electrode slurry, the content of the dispersant in the positive electrode slurry may be greater than about 0.05 parts by weight and less than 0.4 parts by weight.
[0151] In one embodiment of the present disclosure, the negative electrode slurry used to prepare the negative electrode active material layer may include a dispersant, and the dispersant may be a pyrrolidone compound. For example, the dispersant may be polyvinyl pyrrolidone (Junsei, Japan).
[0152] According to one embodiment of the present disclosure, based on 100 parts by weight of the negative electrode slurry, the content of the dispersant in the negative electrode slurry may be greater than about 0 parts by weight and less than 0.5 parts by weight. For example, based on 100 parts by weight of the negative electrode slurry, the content of the dispersant in the negative electrode slurry may be greater than about 0.05 parts by weight and less than 0.4 parts by weight.
[0153] According to one embodiment of the present disclosure, the electrochemical device prepared as described above is installed in a suitable case, and an electrolyte is injected into the case to manufacture a battery.
[0154] According to one embodiment of the present disclosure, the electrolyte may be a + B - The electrolyte obtained by dissolving or dissociating a salt of a structure in an organic solvent, wherein A + Including by Li + 、Na + , K + Ions composed of alkali metal cations or their combinations, B - Included by PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、C(CF2SO2)3 -The organic solvent includes propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone (gamma-butyrolactone), or a mixture thereof, but is not limited thereto.
[0155] One embodiment of the present disclosure provides a battery module including a battery containing the above electrochemical device as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Examples of the device include, but are not limited to, electric tools driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0156] The present disclosure will be described in detail using examples below. However, the embodiments according to the present disclosure can be modified in various ways, and the scope of the present disclosure should not be interpreted as being limited to examples. Examples will be described below to more fully describe the present invention to those of ordinary skill in the art.
[0157] <Example 1>
[0158] 30 parts by weight of a polymer resin (polyethylene resin, Mw: 800,000) having a weight average molecular weight logarithm (Log Mw) of 5.5 and 70 parts by weight of liquid paraffin oil (kinematic viscosity at 40°C: 40 cSt) are introduced into a twin-shaft extruder, kneaded, and then extruded. The extruded polymer resin is formed into a sheet by a T-die and a cooling casting roll, and then biaxially stretched by a tenter-type synchronous stretching machine, first MD stretching and then TD stretching. The liquid paraffin oil used as a diluent is extracted from the stretched sheet using dichloromethane, and the sheet is heat-fixed at 128°C to produce a porous polymer substrate. When preparing the polyethylene film in Example 1, propylene is not added during the polymerization process to increase the crystal content and thus enhance the compression resistance.
[0159] For the porous polymer substrate, the weight average molecular weight of the eluate is obtained using a TREF instrument from Polymer Char. For example, a sample of 40 mg of the porous polymer substrate is prepared, dissolved in 20 mL of trichlorobenzene solvent at 150 ° C for 120 minutes, and then stabilized at 100 ° C for 45 minutes. Then, the sample is introduced into the TREF column, cooled to 35 ° C at a constant rate of 0.5 ° C / min, and kept for 15 minutes. Then, the sample is heated from 35 ° C to 80 ° C at a constant rate of 20 ° C / min, while keeping it at every 5 ° C increment for 20 minutes, and then heated from 80 ° C to 120 ° C at a constant rate of 20 ° C / min, while keeping it at every 2 ° C increment for 20 minutes. Thereafter, the weight average molecular weight of the polymer sample eluted at 98 ° C is measured while the trichlorobenzene solvent flows into the column at a flow rate of 0.5 mL / min.
[0160] Furthermore, the polydispersity index was calculated by the following Formula 3 using the weight average molecular weight measured for the porous polymer substrate and the number average molecular weight obtained by GPC (gel permeation chromatography) analysis.
[0161] [Formula 3]
[0162] Polydispersity Index (PDI) = (weight average molecular weight) / (number average molecular weight)
[0163] The Log value (Log Mw) of the weight average molecular weight of the porous polymer substrate eluate was 5.5, and the polydispersity index (PDI) of the porous polymer substrate eluate was 6.0.
[0164] <Example 2>
[0165] A porous polymer substrate was prepared in the same manner as in Example 1, except that the LogMw of the polymer resin was 6.2.
[0166] <Example 3>
[0167] A porous polymer substrate was prepared in the same manner as in Example 1, except that the polymer resin had a LogMw of 5.1 and a polydispersity index (PDI) of 5.2.
[0168] <Example 4>
[0169] A porous polymer substrate was prepared in the same manner as in Example 1, except that the polymer resin had a LogMw of 5.1 and a polydispersity index (PDI) of 9.9.
[0170] <Comparative Example 1>
[0171] A porous polymer substrate was manufactured in the same manner as in Example 1, except that, compared to Example 1 in which no propylene was added during the polymerization of the polyethylene resin, in Comparative Example 1, approximately 7 parts by weight of propylene was added based on 100 parts by weight of ethylene during the polymerization of the polyethylene resin to prepare a polymer resin (Mw: 800,000), and the Log Mw of the polymer resin was 2.9.
[0172] <Comparative Example 2>
[0173] A porous polymer substrate was manufactured in the same manner as in Example 1, except that, compared to Example 1 in which propylene was not added during the polymerization of the polyethylene resin, in Comparative Example 2, 5.5 parts by weight of propylene was added based on 100 parts by weight of ethylene during the polymerization of the polyethylene resin to prepare a polymer resin (Mw: 800,000), and the LogMw of the polymer resin was 4.4.
[0174] <Comparative Example 3>
[0175] A porous polymer substrate was manufactured in the same manner as in Example 1, except that, compared to Example 1 in which propylene was not added during the polymerization of the polyethylene resin, in Comparative Example 3, 3 parts by weight of propylene were added based on 100 parts by weight of ethylene during the polymerization of the polyethylene resin to prepare a polymer resin (Mw: 800,000), and the Log Mw of the polymer resin was 5.1 and the polydispersity index (PDI) was 2.3.
[0176] <Comparative Example 4>
[0177] A porous polymer substrate was manufactured in the same manner as in Example 1, except that, compared to Example 1 in which propylene was not added during the polymerization of the polyethylene resin, in Comparative Example 4, 1.5 parts by weight of propylene was added based on 100 parts by weight of ethylene during the polymerization of the polyethylene resin to prepare a polymer resin (Mw: 800,000), and the Log Mw of the polymer resin was 5.1 and the polydispersity index (PDI) was 3.9.
[0178] <Experimental Example 1: Measurement of Thickness Reduction Rate>
[0179] For each of the porous polymer substrates of Examples 1 to 4 and Comparative Examples 1 to 4, a contact thickness gauge (VL-50S-B manufactured by Mitutoyo Co., Ltd.) was used to measure the thickness before applying pressure and the thickness after applying 8 MPa pressure at 70°C, and the thickness reduction rate of the porous polymer substrate was confirmed according to the following formula 1. During the measurement, the porous substrate was punched out to obtain a 5 cm × 5 cm sample, and the thickness was measured at a total of 5 points, including 4 points at 1 cm from the corners of the sample and 1 point at the center of the sample. In addition, the samples corresponding to the left, middle, and right positions were measured 3 times along the TD direction, and the arithmetic mean obtained was taken as the thickness of the porous polymer substrate.
[0180] [Formula 1]
[0181] Thickness reduction rate (%) = (thickness of porous polymer substrate before pressure application - thickness of porous polymer substrate after pressure application) / thickness of porous polymer substrate before pressure application × 100
[0182]
[0183] It can be confirmed from Table 1 above that in Comparative Examples 1 and 2, the thickness reduction rate of the porous polymer substrate is high due to the low weight average molecular weight, while in Examples 1 and 2, the thickness reduction rate of the porous polymer substrate decreases as the weight average molecular weight increases.
[0184] In addition, it was confirmed that in Comparative Examples 3 and 4, when the weight average molecular weight was the same, the thickness reduction rate of the porous polymer substrate was high due to the low polydispersity index, while in Examples 3 and 4, as the polydispersity index increased, the thickness reduction rate of the porous polymer substrate decreased.
[0185] According to one embodiment of the present disclosure, by adjusting the weight average molecular weight and the polydispersity index of the crystalline polymer resin contained in the porous polymer substrate, the compression resistance may be enhanced and the thickness variation rate may be reduced.
[0186] <Example 5>
[0187] A polyolefin resin (a copolymer of ethylene and propylene in a weight ratio of 96:4, weight average molecular weight: 800,000) and liquid paraffin oil (kinematic viscosity at 40°C: 40 cSt) were mixed in a weight ratio of 3:7, and 5 wt% polypropylene was added based on the total weight of the polyolefin resin. The mixture was introduced into a twin-shaft extruder, kneaded and extruded. The extruded mixture was formed into a sheet through a T-die and a cooling casting roll, and then biaxially stretched by a tenter-type synchronous stretching machine, first MD stretching and then TD stretching. The liquid paraffin oil was extracted from the stretched sheet using dichloromethane, and the sheet was thermally fixed at 128°C to produce a porous polymer substrate (thickness 9 μm).
[0188] <Example 6>
[0189] A polyolefin substrate (thickness 9 μm) was manufactured in the same manner as in Example 5, except that a polyolefin resin (a copolymer comprising ethylene and propylene in a weight ratio of 93:7) and liquid paraffin oil were mixed in a weight ratio of 3:7, and 5 wt % of polypropylene was added based on the total weight of the polyolefin resin.
[0190] <Example 7>
[0191] A polyolefin substrate (thickness 9 μm) was manufactured in the same manner as in Example 5, except that a polyolefin resin (a copolymer comprising ethylene and propylene in a weight ratio of 85:15) and liquid paraffin oil were mixed in a weight ratio of 3:7, and 2 wt % of polypropylene was added based on the total weight of the polyolefin resin.
[0192] <Example 8>
[0193] A polyolefin substrate (thickness 9 μm) was manufactured in the same manner as in Example 5, except that a polyolefin resin (a copolymer comprising ethylene and propylene in a weight ratio of 85:15) and liquid paraffin oil were mixed in a weight ratio of 3:7, and 3.5 wt % of polypropylene was added based on the total weight of the polyolefin resin.
[0194] <Comparative Example 5>
[0195] A polyolefin substrate (thickness 9 μm) was manufactured in the same manner as in Example 5, except that a polyolefin resin (comprising a copolymer of ethylene and propylene at a weight ratio of 70:30) and liquid paraffin oil were mixed at a weight ratio of 3:7, and 5 wt % of polypropylene was added based on the total weight of the polyolefin resin.
[0196] <Comparative Example 6>
[0197] A polyolefin substrate (thickness 9 μm) was manufactured in the same manner as in Example 5, except that a polyolefin resin (a copolymer comprising ethylene and propylene in a weight ratio of 85:15) and liquid paraffin oil were mixed in a weight ratio of 3:7, and 7 wt % of polypropylene was added based on the total weight of the polyolefin resin.
[0198] <Experimental Example 2: Confirmation of the Amorphous Polymer Resin Content in Polyolefin Substrate>
[0199] The content of non-crystalline polyolefin polymer resin in the polyolefin substrate of each embodiment and comparative example was confirmed using a TREF instrument from Polymer Char. For example, 40 mg of the polyolefin substrate was dissolved in 20 mL of trichlorobenzene solvent at 150° C. for 120 minutes and then stabilized at 100° C. for 45 minutes. The substrate was introduced into a TREF column, cooled to 35° C. at a constant rate of 0.5° C. / min, and then maintained for 15 minutes. Then, the substrate was heated from 35° C. to 80° C. at a constant rate of 20° C. / min, while maintaining for 20 minutes at every 5° C. increment, and then heated from 80° C. to 120° C. at a constant rate of 20° C. / min, while maintaining for 20 minutes at every 2° C. increment. Then, while allowing the trichlorobenzene solvent to flow into the column at a flow rate of 0.5 mL / min, the weight of the fraction eluted at 35° C. was measured, as shown in Tables 2 and 3 below.
[0200] The average amount of CH3 per 1,000 carbon atoms was also confirmed using an IR detector included in the above instrument, as shown in Tables 2 and 3 below.
[0201] <Experimental Example 3: Confirmation of compression resistance based on the content of amorphous polymer resin in polyolefin substrate>
[0202] For the polyolefin substrates of Examples 5, 6 and Comparative Example 5, an EG01-55-1MR apparatus from Asahi Seico was used to measure the flow rate of 100 cc of air through a 1-inch diameter glass substrate at room temperature under a constant water pressure of 4.8 inches. 2 The time of the sample is to confirm the air permeability before compression.
[0203] The polyolefin substrate was placed in a press and pressed at 70° C. and 8 MPa for 10 seconds. The air permeability after compression was measured using the same equipment and the same method as above.
[0204] Based on the air permeability of the substrate before and after compression, the air permeability increase rate was calculated according to the above formula 2, as shown in the following Table 2.
[0205]
[0206] As shown in Table 2 above, it can be confirmed that the air permeability increase rate of Comparative Example 5 is 364%, while the air permeability increase rates of Examples 5 and 6 are 30% and 68%, respectively.
[0207] <Experimental Example 4: Confirmation of Compression Resistance of Polyolefin Substrate Based on Average Short Chain Branches>
[0208] For the polyolefin substrates of Examples 7 and 8 and Comparative Example 6, the air permeabilities before and after compression were measured in the same manner as in Experimental Example 3.
[0209] Based on the air permeability of the substrate before and after compression, the air permeability increase rate was calculated according to the above formula 2, as shown in the following Table 3.
[0210]
[0211] As shown in Table 3 above, it can be confirmed that the air permeability increase rate of Comparative Example 6 is 201%, while the air permeability increase rates of Examples 7 and 8 are 27% and 147%, respectively.
[0212] <Example 9>
[0213] 30 parts by weight of a polymer resin (polyethylene resin, Mw: 1,500,000) and 70 parts by weight of liquid paraffin oil (kinematic viscosity at 40°C: 40 cSt) were introduced into a biaxial extruder, kneaded, and then extruded. The extruded mixture was formed into a sheet through a T-die and a cooling casting roll, and then biaxially stretched by a tenter-type synchronous stretching machine, first MD stretching and then TD stretching. The liquid paraffin oil used as a diluent was extracted from the stretched sheet using methylene chloride, and the sheet was heat-fixed at 128°C to produce a porous polymer substrate.
[0214] For the porous polymer substrate, the weight ratio of the eluate eluted at 98°C is calculated using a TREF instrument from Polymer Char. For example, a porous polymer substrate sample of 40 mg is prepared, dissolved in 20 mL of trichlorobenzene solvent at 150°C for 120 minutes, and then stabilized at 100°C for 45 minutes. Then, the sample is introduced into the TREF column, cooled to 35°C at a cooling rate of 0.5°C / min, and maintained for 15 minutes. Then, the sample is heated from 35°C to 80°C at a constant rate of 20°C / min, while maintaining for 20 minutes at every 5°C increment, and then heated from 80°C to 120°C at a constant rate of 20°C / min, while maintaining for 20 minutes at every 2°C increment. Subsequently, while the trichlorobenzene solvent flows into the column at a flow rate of 0.5 mL / min, the weight of the polymer sample eluted at 98°C is measured, and the content of the crystalline polymer resin in the porous polymer substrate is 72% by weight.
[0215] <Example 10>
[0216] A porous polymer substrate was prepared in the same manner as in Example 9, except that the content of the crystalline polymer resin in the porous polymer substrate was 83 wt %.
[0217] <Comparative Example 7>
[0218] A porous polymer substrate was prepared in the same manner as in Example 9, except that 7 parts by weight of polypropylene (Mw: 350,000) was added to 100 parts by weight of polyethylene (Mw: 600,000) to prepare a polymer resin (Mw: 580,000), and the content of the crystalline polymer resin in the porous polymer substrate was 66% by weight.
[0219] <Comparative Example 8>
[0220] A porous polymer substrate was prepared in the same manner as in Example 9, except that 0.5 parts by weight of polypropylene (Mw: 350,000) was added to 100 parts by weight of polyethylene (Mw: 600,000) to prepare a polymer resin (Mw: 600,000), and the content of the crystalline polymer resin in the porous polymer substrate was 90% by weight.
[0221] <Experimental Example 5: Measurement of Indentation Depth and Standard Deviation>
[0222] Using a nanoindenter (Fischerscope, HM2000), a Vickers indenter (tip width of 0.5 μm) was pressed into the porous polymer substrate with a force of 100 nN, and then the indentation depth was measured by atomic force microscopy (AFM).
[0223] For the surfaces of the porous polymer substrates of Examples 9 and 10 and Comparative Examples 7 and 8, Dimension Icon (manufactured by Bruker Corporation) was set to the following conditions: Figure 1 As shown, the peak tapping force was measured while moving the tip relative to each sample surface, and an atomic force microscope (AFM, OSTASPA-R3, Bruker, f=300 kHz, k=26 N / m) was used to measure the depth to which the tip penetrated the sample surface when the peak tapping force was measured.
[0224] -Mode: Tapping (peak force QNM)
[0225] - Scanning speed: 0.3 Hz
[0226] -Peak force set point: 100 nN, Amplitude: 300 nm
[0227] - Scanning angle: 90°
[0228] <Experimental Example 6: Measurement of Insulation Breakdown Voltage>
[0229] For Examples 9 and 10 and Comparative Examples 7 and 8 having a thickness of 12 μm, a pressure of 8 MPa was applied at 70° C., and then the voltage was measured when the current exceeded 0.5 mA and 3 seconds while increasing the voltage at a rate of 100 mV / s.
[0230]
[0231] It can be confirmed from Table 4 above that in Examples 9 and 10, the content of crystalline polymer resin in the porous polymer substrate is above the reference value, which is appropriate, so that the indentation depth is relatively low and the standard deviation of the indentation depth is reduced, thereby increasing the insulation breakdown voltage after compression.
[0232] On the other hand, it can be confirmed that in Comparative Example 7, the content of the crystalline polymer resin in the porous polymer substrate is small, which is 66 weight %, so that the indentation depth increases sharply, and therefore the insulation breakdown voltage after compression is less than 1,000 V, and the increase is relatively small, while in Comparative Example 8, the content of the crystalline polymer resin in the porous polymer substrate is excessive, which is 90 weight %, so that the standard deviation of the indentation depth increases, and therefore the insulation breakdown voltage after compression is less than 1,000 V, and the increase is relatively small.
[0233] Therefore, the separator for an electrochemical device according to an embodiment of the present disclosure can adjust the content of the crystalline polymer resin in the porous polymer substrate to adjust the indentation depth and its standard deviation, thereby improving the insulation breakdown voltage after lamination.
[0234] As can be seen from the above, various embodiments of the present disclosure have been described herein for illustrative purposes, and various modifications may be made without departing from the scope and spirit of the present disclosure. Therefore, the various embodiments disclosed herein are not intended to be limiting, and the actual scope and spirit are specified by the appended claims.
Claims
1. A diaphragm for an electrochemical device, the diaphragm comprising: Porous polymer substrate, in, The porous polymer substrate comprises a non-crystalline polymer resin and a crystalline polymer resin, and The eluate eluted from the porous polymer substrate by the temperature rising elution fractionation (TREF) method has a weight average molecular weight (Mw) of 100,000 or more.
2. The electrochemical device separator according to claim 1, wherein The porous polymer substrate contains 40 wt % or less of a fraction eluted by a TREF method at a temperature of 35° C. or less.
3. The separator for an electrochemical device according to claim 1, wherein The content of the non-crystalline polymer resin in the porous polymer substrate is 40 wt % or less.
4. The electrochemical device separator according to claim 1, wherein The content of the crystalline polymer resin in the porous polymer substrate is 60 wt % or more.
5. The separator for an electrochemical device according to claim 1, wherein The weight ratio of the non-crystalline polymer resin to the crystalline polymer resin in the porous polymer substrate is 1:1 to 10:
1.
6. The separator for an electrochemical device according to claim 1, wherein The porous polymer substrate has an indentation depth deviation of -5 nm to 5 nm.
7. The separator for an electrochemical device according to claim 1, wherein The porous polymer substrate comprises a polyolefin resin, The non-crystalline polymer resin is a non-crystalline polyolefin resin, and The crystalline polymer resin is a crystalline polyolefin-based resin.
8. The separator for an electrochemical device according to claim 7, wherein The polyolefin resin is one selected from the group consisting of polyethylene, polypropylene, polybutene, polypentene, polyhexene, polyoctene, copolymers of one or more of ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene, and combinations thereof.
9. The separator for an electrochemical device according to claim 7, wherein The polyolefin-based resin has an average of 500 or less short chain branches (SCB) per total 1,000 carbon atoms.
10. The separator for an electrochemical device according to claim 7, wherein The polyolefin resin has a melt index (ASTM D1238, 190° C., 2.16 kg) of 0.1 g / 10 min to 0.3 g / 10 min.
11. The separator for an electrochemical device according to claim 1, wherein The porous polymer substrate has a weight average molecular weight (Mw) of 500,000 to 3,000,000.
12. The separator for an electrochemical device according to claim 1, wherein The polydispersity index (PDI) of the eluate is 5 or more.
13. The separator for an electrochemical device according to claim 1, wherein When a pressure of 8 MPa is applied at 70°C, at least one of the following conditions (i) to (iii) is satisfied: (i) the thickness reduction rate of the porous polymer substrate defined by the following formula 1 is 10% or less: [Formula 1] Thickness reduction rate (%) = (thickness of porous polymer substrate before applying pressure - thickness of porous polymer substrate after applying pressure) / thickness of porous polymer substrate before applying pressure × 100; (ii) the post-compression air permeability increase rate of the porous polymer substrate defined by the following formula 2 is 185% or less: [Formula 2] Air permeability increase rate (%) = (air permeability after compression - air permeability before compression) / (air permeability before compression) × 100; and (iii) The porous polymer substrate has a dielectric breakdown voltage of 1,000 V or more.
14. The separator for an electrochemical device according to claim 1, wherein The porous polymer substrate has a thickness of 1 μm to 30 μm.
15. An electrochemical device comprising: positive electrode; a negative electrode; and The separator according to claim 1, wherein the separator is interposed between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Positioning Reference Signal (PRS) bundling across multiple discontinuous reception (MULTI-DRX) groups
KR1020230051176A
Device for generating aerosol
KR1020230055916A
Organic-inorganic nano-polymer composite film introduced with organic precursor and redox flow battery comprising the same and method for manufacturing the same
KR1020230065754A
